Nghiên cứu tương tác của muối Zeise với axit eugenoxyaxetic trong ancol. - Đà, Trần Thị; Mai, Trương Thị Cẩm; Thư, Trần Thị Kim; Đĩnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2012)
An esterification in the coordination sphere of platinum(II) is reported for the fist time. The reaction of Zeise’s salt and eugenoxyacetic acid in an alcohol leads to formation of complexes containing either eugenoxyacetic acid or alkyl eugenoxyacetate. The structure of formed complexes were confirmed by elemental analysis, IR, MS and NMR spectroscopy. It is shown that h2-coordinated buthyl eugenoxyacetate was deprotonated to form a Pt-C(aryl) bond.